(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role and significance of international cooperation in the preparation of specialists in higher education. The interrelations between global education systems, experience exchange, and innovative methodologies are crucial factors that significantly contribute to improving the quality of education and producing highly qualified specialists. The article examines how the effectiveness of educational and scientific cooperation can be enhanced, as well as the role of international collaboration in preparing professionals who meet the demands of the global labor market. Furthermore, the article discusses Uzbekistan’s participation in international education systems, its role in global academic partnerships, and future perspectives for strengthening international cooperation in the field of higher education.